2021
DOI: 10.1172/jci.insight.143251
|View full text |Cite
|
Sign up to set email alerts
|

Kcnj16 knockout produces audiogenic seizures in the Dahl salt-sensitive rat

Abstract: Kir5.1 is an inwardly rectifying potassium (Kir) channel subunit abundantly expressed in the kidney and brain. We previously established the physiologic consequences of a Kcnj16 (gene encoding Kir5.1) knockout in the Dahl SS rat (SS Kcnj16-/-), which caused electrolyte/pH dysregulation and high salt dietinduced mortality. Since Kir channel gene mutations may alter neuronal excitability and are linked to human seizure disorders, we hypothesized that SS Kcnj16-/rats would exhibit neurological phenotypes, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Animals were place in a custom-made calibrated whole-body plethysmograph chamber designed for long-term housing to record breathing as described previously ( Manis et al, 2021 ). Briefly, animals were placed in the plexiglass chamber and allowed to acclimate overnight prior to initiating recording 24 h later.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were place in a custom-made calibrated whole-body plethysmograph chamber designed for long-term housing to record breathing as described previously ( Manis et al, 2021 ). Briefly, animals were placed in the plexiglass chamber and allowed to acclimate overnight prior to initiating recording 24 h later.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies are reported in compliance with the ARRIVE guidelines (Percie du Sert et al, 2020) and with the recommendations made by the British Journal of Pharmacology (Lilley et al, 2020; McGrath & Lilley, 2015). The re‐derived Rapp Dahl SS (RRID:RGD_69369) rat used in our studies (SS/JrHsdMcwi) has been inbred for more than 50 generations at the Medical College of Wisconsin and used to compare the outcomes of pharmacological inhibition of K ir channels with results obtained earlier in the same SS strain with a null mutation of Kcnj16 (Manis et al, 2019; Manis et al, 2021; Palygin et al, 2017). Eight‐ to 12‐week‐old male SS rats (TBW approximately 220 g) were used.…”
Section: Methodsmentioning
confidence: 99%
“…This is interesting because Kir4.1 channels can heteromerize with Kir5.1 to form a CO 2 /H + sensitive conductance (Xu et al, 2000 ), and recent work showed that both Kir4.1 and Kir5.1 transcript are expressed by medullary serotonergic raphe neurons and so may contribute to CO 2 /H + detection by these putative chemoreceptors (Puissant et al, 2017 ). Moreover, loss of Kir5.1 ( Kcnj16 gene) resulted in an audiogenic seizure phenotype with increased mortality in a rat model of salt-sensitive hypertension and chronic kidney disease (Manis et al, 2021 ), probably by a mechanism involving disruption of heteromeric Kir4.1/5.1 channels since Kir5.1 does not form functional homomeric channels (Pessia et al, 1996 ). Therefore, disruption of homo or heteromeric Kir4.1 channels may be a common substrate for breathing problems and seizure propensity.…”
Section: Spreading Depolarizationmentioning
confidence: 99%